2001
DOI: 10.1046/j.1365-2591.2001.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of oxidative potential water as a root canal irrigant

Abstract: The most effective irrigation technique for smear removal was 15% EDTA irrigation by means of syringe following instrumentation with 5% NaOCl solution. However, the most effective irrigation technique for debris removal was ultrasonic irrigation regardless of irrigant used. OPW irrigation by means of syringe following instrumentation with 5% NaOCl showed a similar effect to that of 15% EDTA irrigation for removal of smear layer and debris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 16 publications
1
31
0
10
Order By: Relevance
“…24 Likewise, a study by Hata et al showed that instrumentation and irrigation with 5% sodium hypochlorite followed by 15% EDTA using a syringe was the most effective irrigation technique for smear layer removal. 25 Therefore, in the current study, conventional irrigation and smear layer removal by the aforementioned protocol was considered as the gold standard for comparison. Since mechanical instrumentation only eliminates 50% of bacteria from root canal, irrigating solutions are required to eliminate microbiota from the zones out of reach of instruments.…”
Section: Discussionmentioning
confidence: 99%
“…24 Likewise, a study by Hata et al showed that instrumentation and irrigation with 5% sodium hypochlorite followed by 15% EDTA using a syringe was the most effective irrigation technique for smear layer removal. 25 Therefore, in the current study, conventional irrigation and smear layer removal by the aforementioned protocol was considered as the gold standard for comparison. Since mechanical instrumentation only eliminates 50% of bacteria from root canal, irrigating solutions are required to eliminate microbiota from the zones out of reach of instruments.…”
Section: Discussionmentioning
confidence: 99%
“…EDTA or NaOCl [27,127,128]. The discrepancies in the literature are likely due to the method of delivery, and this has been suggested to be the critical treatment factor [128,129].…”
Section: (I) Treatment and Prevention Of Wound Infectionmentioning
confidence: 99%
“…Earlier studies found ECA solution to be effective in removing the smear layer. 68,69 In view of its safety compared with NaOCl, ECA solutions may have potential as a root canal irrigant and warrant further investigation.…”
Section: Future Development In Root Canal Irrigationmentioning
confidence: 99%